Temporal Summation of Heat Pain in Temporomandibular Disorder Patients - Raphael, Karen G. (2009)
AIMS: One possible mechanism underlying myofascial temporomandibular disorders (TMD) is altered central nervous system processing of painful stimuli. The current study aimed to compare TMD cases to controls on two measures of central processing, i.e., temporal summation of heat pain and decay of subsequent aftersensations, following thermal stimulation in both a trigeminal and extratrigeminal area. METHODS: Using a “wind-up” (WU) protocol, 19 female TMD patients and 17 controls were exposed to 15 heat stimuli at a rate of 0.3 Hz. Numeric pain ratings were elicited after the 1(st), 5(th), 10(th) and 15(th) stimulus presentation and every 15 seconds after final presentation (aftersensations), for up to 2 minutes. In separate trials, the thermode was placed on the thenar eminence of the hand and the skin overlying the masseter muscle. RESULTS: Groups did not differ with respect to the slope of WU when stimulated at either anatomic site, although asymptote occurred sooner for TMD patients than controls. In analysis of aftersensations, a significant group x site x time interaction was detected, in which TMD patients experienced more prolonged painful aftersensations than controls when stimulated on the skin overlying the masseter muscles. CONCLUSIONS: These results are consistent with the presence of enhanced central sensitivity in TMD and suggest that this sensitivity may be largely confined to the region of clinical pain. This contrasts with conditions such as fibromyalgia, where central sensitivity appears to be widespread.